Does blockchain technology democratize entrepreneurial finance? An empirical comparison of ICOs, venture capital, and REITs. Issue 1 (17th February 2022) - Fisch, Christian; Meoli, Michele; Vismara, Silvio
ABSTRACT: Initial coin offerings (ICOs) are one of the major innovations that characterize the digital revolution of financial markets. Among the expectations created by the digital revolution is the democratization of entrepreneurial finance, defined in terms of the creation of more equality regarding the access to financial resources by categories known to be underrepresented among potential entrepreneurs. Following this line of research, we investigate, through two complementary empirical studies, whether gender, ethnicity, and geography affect the choice of ICOs vs. traditional financing alternatives. Additionally, we assess whether these characteristics increase the amount of money an entrepreneur can raise. In Study I, we compare 390 ICO ventures to a sample of 1, 078 VC-backed blockchain ventures, identifying a negative correlation between the choice of an ICO (vs. VC-backing) and a location in an urban area. In Study II, we compare 160 ICO ventures to 163 real estate investment trusts (REITs), reaffirming the results of Study I. The findings show significant participation and likelihood of successful campaigns for ethnical minorities in ICOs, with the latter also being able to collect, ceteris paribus, larger amounts of funding. In contrast, female entrepreneurs do not have higher chances to participate nor raise funds in ICOs.